Clinical features of progressive supranuclear palsy - Wen, Yafei; Yang, Qijie; Jiao, Bin; Zhang, Weiwei; Lin, Jingyi; Zhu, Yuan; Xu, Qian; Zhou, Hui; Weng, Ling; Liao, Xinxin; Zhou, Yafang; Wang, Junling; et al. (Frontiers in Aging Neuroscience, 2023)
Background: Progressive supranuclear palsy (PSP) is a clinically heterogenous atypical parkinsonian syndrome. Therefore, early recognition and correct diagnosis of PSP is challenging but essential. This study aims to characterize the clinical manifestations, magnetic resonance imaging (MRI), and longitudinal MRI changes of PSP in China.Method: Clinical and MRI presentations were compared among 150 cases with PSP. Then the longitudinal MRI changes among 20 patients with PSP were further explored. Additionally, a series of midbrain-based MRI parameters was compared between PSP-P and PD.Results: Throughout the course of the disease, there were differences in the symptoms of the fall and hand tremor between the PSP-RS and PSP-P. There were significant differences in the six midbrain-based MRI parameters between the PSP-RS and the PSP-P, including hummingbird sign, midbrain diameter, midbrain to pons ratio (MTPR), midbrain area, midbrain area to pons area ratio (Ma/Pa), and midbrain tegmental length (MBTegm). Longitudinal MRI studies revealed that the annual rel.ΔMTPR and rel.Δ(Ma/Pa) for PSP were 5.55% and 6.52%, respectively; additionally, PSP-RS presented a higher decline rate than PSP-P.Moreover, MTPR ≤ 0.56, midbrain diameter ≤ 0.92, midbrain area ≤ 1.00, and third ventricle width ≤ 0.75 could identify PSP-P from PD.Conclusion: PSP-P differs from PSP-RS regarding clinical manifestations, MRI, and longitudinal MRI changes. MRI parameters could be potential imaging markers to identify PSP-P from PD.